Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12887-016-0626-6
|View full text |Cite
|
Sign up to set email alerts
|

GM2 gangliosidosis AB variant: novel mutation from India – a case report with a review

Abstract: BackgroundGM2 gangliosidosis-AB variants a rare autosomal recessive neurodegenerative disorder occurring due to deficiency of GM2 activator protein resulting from the mutation in GM2A gene. Only seven mutations in nine cases have been reported from different population except India.Case presentationPresent case is a one year old male born to 3rd degree consanguineous Indian parents from Maharashtra. He was presented with global developmental delay, hypotonia and sensitive to hyperacusis. Horizontal nystagmus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…All of them are novel SNPs except C138R which is reported in previous studies. Sheth et al (2016) and Kochumon et al (2017) studies are agrre with us that C138R found in GM2A gene and associated with AB variant of GM2 gangliosidosis (22,45).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…All of them are novel SNPs except C138R which is reported in previous studies. Sheth et al (2016) and Kochumon et al (2017) studies are agrre with us that C138R found in GM2A gene and associated with AB variant of GM2 gangliosidosis (22,45).…”
Section: Discussionmentioning
confidence: 61%
“…(10, 11) located in chromosome 5q31.3-q33.1 (12)(13)(14) The GM2 activator deficiency is caused by mutations in the GM2A gene encoding the GM2 activator protein. (15) Different mutations have been reported related to GM2A, (16)(17)(18)(19)(20)(21)(22) but interestingly, some study shows that, mutation in GM2A Leads to a Progressive Chorea-dementia Syndrome. (23) ELISA system can be used as diagnosis tool as well as therapeutic evaluation of GM2 gangliosidoses using anti-GM2 ganglioside antibodies (24) Can also be diagnosed by demonstrating accumulation of GM2 in the CSF of patients with normal hexosaminidase activity.…”
Section: Introductionmentioning
confidence: 99%
“…4 Ten patients with molecularly proven AB variant, including eight different GM2A gene mutations, have been described in the literature. 3 Our patients showed symptoms of infantile degenerative disease. After an extensive diagnostic work-up including enzymatic and genetic testing for gangliosidosis, which did not show specific findings, finally, genetic analysis for GM2 gangliosidosis AB variant elucidated the cause of the disease on the basis of clinical characteristics in both.…”
Section: Discussionmentioning
confidence: 64%
“…To the best of our knowledge, 10 molecularly proven patients with eight different mutations have been reported so far. 3 We present two patients with the rare AB variant of the disease showing clinical courses similar to the rapidly progressive infantile TSD with different magnetic resonance imaging (MRI) presentations and report a novel frameshift mutation of the GM2A gene.…”
Section: Introductionmentioning
confidence: 98%
“…1,2 Only 16 patients with GM2 Activator protein deficiency have been reported so far and the underlying mutation was proven in only 9 cases. [3][4][5][6][7][8][9][10][11] We report a homozygous intronic mutation proven case of GM2 activator protein deficiency which is the 10th case report proven by molecular studies.…”
Section: Introductionmentioning
confidence: 99%